2019
DOI: 10.1186/s12936-019-2855-2
|View full text |Cite
|
Sign up to set email alerts
|

Human behaviour and residual malaria transmission in Zanzibar: findings from in-depth interviews and direct observation of community events

Abstract: Background Zanzibar has maintained malaria prevalence below 1% for the past decade, yet elimination remains elusive despite high coverage of core vector control interventions. As part of a study investigating the magnitude and drivers of residual transmission in Zanzibar, qualitative methods were utilized to better understand night time activities and sleeping patterns, individual and community-level risk perceptions, and malaria prevention practices. Methods A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 24 publications
2
70
0
Order By: Relevance
“…Furthermore, most respondents reported night-time communal ceremonies/gatherings, which may take more than three days. Similar observations are increasingly documented in many other malaria endemic resource-poor settings [17,43,[44][45][46]. Cooking and communal ceremonies/gatherings have been reported among the popular activities that kept people outdoors in many endemic areas of Africa notably Kilombero Valley, southern Tanzania [17,44,47], Unguja Island, Zanzibar [46], northern…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Furthermore, most respondents reported night-time communal ceremonies/gatherings, which may take more than three days. Similar observations are increasingly documented in many other malaria endemic resource-poor settings [17,43,[44][45][46]. Cooking and communal ceremonies/gatherings have been reported among the popular activities that kept people outdoors in many endemic areas of Africa notably Kilombero Valley, southern Tanzania [17,44,47], Unguja Island, Zanzibar [46], northern…”
Section: Discussionsupporting
confidence: 61%
“…Tanzania [17,44,46] and elsewhere in Africa [43,45,48], respondents reported little or no protection at all during outdoor activities at or away from home. Purportedly, the study communities experience a high risk of malaria because the documented night-time outdoor activities take long periods which may coincide with vector's peak biting time.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly little is known of the short-and long-term impacts of different control methods on host choice.The introduction of indoor residual spraying and insecticidal nets has resulted in a change in the biting behaviour of major malaria vectors with many mosquito species seeking a higher proportion of blood meals outdoors 3-6 and/or from non-human hosts 7-10 . Coupled with increasing rates of insecticide resistance 11 , these behavioural changes indicate potential inadequacies of current leading vector-control tools to target outdoor biting and, correspondingly, sustained residual malaria transmission [12][13][14][15][16][17][18][19] . Therefore, understanding this behaviour is becoming increasingly important when implementing vector control strategies.In the field, which host is ultimately bitten is a complex balance between intrinsic (genetic) and extrinsic (environmental) factors including behavioural conditioning driven by exposure to insecticides or previous successful feeds from a particular host 20,21 .…”
mentioning
confidence: 99%
“…A strength of this study is that behaviours at home and during travel within the same individuals were prospectively compared, minimizing the potential for confounding. Similar studies have only assessed malaria-relevant behaviours while travelling, or at home, but not both [23,41,42]. A study conducted in south-eastern Tanzania evaluated human behaviour of participants at home [20].…”
Section: Discussionmentioning
confidence: 99%
“…Although travellers may be at increased risk of malaria due to exposure to higher malaria transmission [18,19], changes in behaviour while away from home may also contribute. Some studies have suggested that individuals who travel within malaria-endemic areas may take part in outdoor activities, go to bed late, and be less likely to use LLINs, all behaviours that increase exposure to mosquitoes and risk of malaria infection [20][21][22][23]. To further explore associations between overnight travel and behaviours that might modify the risk of malaria infection, data collected over a two-year period from a cohort of individuals living in Tororo, Uganda, were analysed.…”
Section: Introductionmentioning
confidence: 99%